Exploring the short-term and long-term relationships between climate and human development - Maurizio Malpede; Marco Percoco (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2021)
How global warming affects human development is a central question for economists as well as social scientists. While most of the literature has focused on the impact of rainfall and temperatures on individual well-being, precipitations alone do not capture the actual soil water availability, which also depends on the potential evaporation of the water. This paper considers shocks in precipitation, temperature, and an original measure of soil aridity to exploit the association between climate warming and Human Development. While precipitations do not have a significant long-term impact on human development growth, both temperature and potential evapo-transpiration shocks affect two of the three determinants of the Human Development Index, namely life expectancy at birth and education.
Keywords: 330; Human Development; Weather Shocks; Soil Aridification; Africa